Secondary School Students' Performance and Opinions Towards Activities Based on Engineering Design Process - YILDIRIM, MEHTAP (CUKUROVA UNIV, 2018)
The purpose of this study was to investigate secondary school students' performance and views in activities based on the engineering design process. From the two selected secondary schools, 48 students voluntarily participated in this study. For each school, six students were selected from each of the grades 5, 6, 7, and 8. In this study, a case study approach was used which is one of the types of qualitative research design. Four different situations were considered from a holistic approach in two different schools. To obtain the data, qualitative data collection techniques were chosen. The observation, interview forms were analysed through descriptive analysis. Two researchers implemented the activities based on the engineering design process to all the groups. In the first week, the students were informed about the engineering design process. The following weeks, the students worked in groups and undertook the activities designed by the researchers for each grade level in accordance with the relevant units. The results of this study revealed that students at lower grades had difficulty identifying the problem, obtaining the data, drawing the design, using the materials, and redesigning steps. However, all the students had positive views related to the implementation of the engineering design process.
Keywords: Engineering Design Process; Secondary School; Students' Performances; SCIENCE; CLASSROOMS; EDUCATION